Holle list : vocabularies in languages of Indonesia Vol.3/1. Shouthern Moluccas ; central moluccas : Seram (I), (materials in languages of Indonesia. No.4) - Stokhof, W. A. L. (The Australian National University, 1981)
iv, 209 p.; 25 cm.